Around Australia at 80ks : two humans, one dog and a bright yellow kombi on the road trip of a lifetime - Schofield, Meredith (Boon Wurrung Country, South Melbourne, Vic. : Affirm Press, 2021)
Mez, Sean, their rescue pup, Bandit, and their beloved yellow kombi, Etta, are on an epic road trip around Australia. And they're taking you with them. Around Australia at 80ks follows this motley quartet's adventures and misadventures as they make their way around our great southern land. Bursting with inspiration, insider tips, dog-friendly travel advice and stunning photography, this book is the holiday we all need.
Keywords: Schofield, Meredith -- Travel -- Australia; Travel writing -- Australia; Australia -- Description and travel; Australia -- Pictorial works; Australian